ADAPTIVE LEADERSHIP IN THE ERA OF DISRUPTION: MANAGING TEAM WITH FLEXIBILITY - Sidrotun Naim (Adisam Publisher, 2025)
Era of disruption demand every leader For manage his team with flexibility, through application leadership adaptive. Study This aim For identify and analyze problem in apply leadership adaptive and defining effective strategy in management team in environment dynamic organization. Through study literature, analysis show that leadership adaptive need approach holistic and adaptive that pays attention dynamics psychological individual, ability analytical, interpersonal skills, management source dynamic power, as well development capacity inclusive leadership. Research result recommend necessity investment in training, development, and support for leader as well as member team For overcome challenge and exploit opportunity. Strategy main covers define vision, recognize uniqueness team, building environment learn, adapt to change, communication two direction, as well leadership share. Study This expected can give outlook in formulate strategy leadership Effective adaptation in an era of disruption.